2014
DOI: 10.1177/0886109914531957
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Black Women’s Experiences in Drug Abuse and Mental Health Services

Abstract: Little is known about black women's perceptions of service barriers in mental health and substance treatment. This article reports the findings of a qualitative study that explored the perceptions of 29 black women who received treatment in a small urban Northeastern city. Findings of the focus group data revealed participants' experiences of services as discussed through the themes of bias and stigma; incompatible perspectives of wellness versus illness between consumer and provider; consumer mistrust; and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 49 publications
(69 reference statements)
1
48
0
Order By: Relevance
“…Treatment readiness barriers were identified as issues that focused on fear of seeking treatment (guilt or shame), lack of motivation for treatment (personal), the belief that treatment was not needed (personal), and the obstacle of interpersonal relationships with family and childcare (interpersonal reasons) (see Table ). For Personal barriers women often delayed or avoided treatment because they changed their mind, wanted to manage on their own, or had problems making arrangements (Allen, ; Brown, ; Ehrmin, ; Hser, Maglione, Polinsky, & Anglin, ; Jones, Hopson, Warner, Hardiman, & James, ; MacMaster, ; Roberts & Nishimoto, ; Rosen, Tolman, & Warner, ). Interpersonal barriers were more specific to caring for children, a spouse/partner, and other family members.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment readiness barriers were identified as issues that focused on fear of seeking treatment (guilt or shame), lack of motivation for treatment (personal), the belief that treatment was not needed (personal), and the obstacle of interpersonal relationships with family and childcare (interpersonal reasons) (see Table ). For Personal barriers women often delayed or avoided treatment because they changed their mind, wanted to manage on their own, or had problems making arrangements (Allen, ; Brown, ; Ehrmin, ; Hser, Maglione, Polinsky, & Anglin, ; Jones, Hopson, Warner, Hardiman, & James, ; MacMaster, ; Roberts & Nishimoto, ; Rosen, Tolman, & Warner, ). Interpersonal barriers were more specific to caring for children, a spouse/partner, and other family members.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported social support or interpersonal issues as barriers to treatment (Allen, 1995;Jones et al, 2015, MacMaster, 2005Roberts & Nishimoto, 2006). Allen (1995) found that participant's role as a wife and mother interfered with seeking treatment.…”
Section: Treatment Readiness Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that this population (minority women with SUDs) might not want to disclose trauma (possibly due to cultural barriers, guardedness, embarrassment, and/or provider mistrust, etc. ), 22,[25][26][27]35 and is shown to have poorer outcomes, disproportionate physical health burdens, and greater rates of addiction severity, compared to those without trauma or PTSD, 9 it is important to find ways to identify women for further evaluation and referral. The study found that six items, taken from non-PTSD-specific symptom measures, when calculated together, are associated with a probable PTSD diagnosis with a sensitivity of 88.7%, a specificity of 66.7%, a positive predictive value of 73.4%, a negative predictive value of 85.0%, and an accuracy of 77.9%.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, African American women may be particularly guarded around reporting symptoms, 25 as African American individuals have reported mistrust of providers and described providers as insensitive and lacking cultural awareness. 26,27 Thus, a negative view of providers could impede the disclosure, and subsequent treatment, of symptoms, particularly in the context of substance treatment. 24 In broader medical care settings, substance use frequently goes undetected, due to provider lack of knowledge, skills, confidence, [28][29][30] and time.…”
Section: Introductionmentioning
confidence: 99%